Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 201888 by MrGHK last updated on 15/Dec/23

Answered by namphamduc last updated on 15/Dec/23

S=Σ_(n=0) ^∞ ((ψ(n+2))/((n+2)^2 ))=Σ_(n=1) ^∞ ((ψ(n+1))/((n+1)^2 ))=Σ_(n=1) ^∞ ((H_n −γ)/((n+1)^2 ))  =−γ((π^2 /6)−1) +Σ_(n=1) ^∞ (H_n /((n+1)^2 ))  ∗Σ_(n=1) ^∞ (H_n /((n+1)^2 ))=Σ_(n=1) ^∞ ((H_(n+1) −(1/(n+1)))/((n+1)^2 ))=−ζ(3)+1+Σ_(n=1) ^∞ (H_(n+1) /((n+1)^2 ))  =−ζ(3)+Σ_(n=1) ^∞ (H_n /n^2 )=−ζ(3)−Σ_(n=1) ^∞ (1/n)∫_0 ^1 x^(n−1) ln(1−x)dx  =−ζ(3)+∫_0 ^1 ((ln^2 (1−x))/x)dx=−ζ(3)+∫_0 ^1 ((ln^2 (x))/(1−x))dx  =−ζ(3)+2Σ_(n=0) ^∞ (1/((n+1)^3 ))=ζ(3)  ⇒S=ζ(3)−γ((π^2 /6)−1)

$${S}=\underset{{n}=\mathrm{0}} {\overset{\infty} {\sum}}\frac{\psi\left({n}+\mathrm{2}\right)}{\left({n}+\mathrm{2}\right)^{\mathrm{2}} }=\underset{{n}=\mathrm{1}} {\overset{\infty} {\sum}}\frac{\psi\left({n}+\mathrm{1}\right)}{\left({n}+\mathrm{1}\right)^{\mathrm{2}} }=\underset{{n}=\mathrm{1}} {\overset{\infty} {\sum}}\frac{{H}_{{n}} −\gamma}{\left({n}+\mathrm{1}\right)^{\mathrm{2}} } \\ $$$$=−\gamma\left(\frac{\pi^{\mathrm{2}} }{\mathrm{6}}−\mathrm{1}\right)\:+\underset{{n}=\mathrm{1}} {\overset{\infty} {\sum}}\frac{{H}_{{n}} }{\left({n}+\mathrm{1}\right)^{\mathrm{2}} } \\ $$$$\ast\underset{{n}=\mathrm{1}} {\overset{\infty} {\sum}}\frac{{H}_{{n}} }{\left({n}+\mathrm{1}\right)^{\mathrm{2}} }=\underset{{n}=\mathrm{1}} {\overset{\infty} {\sum}}\frac{{H}_{{n}+\mathrm{1}} −\frac{\mathrm{1}}{{n}+\mathrm{1}}}{\left({n}+\mathrm{1}\right)^{\mathrm{2}} }=−\zeta\left(\mathrm{3}\right)+\mathrm{1}+\underset{{n}=\mathrm{1}} {\overset{\infty} {\sum}}\frac{{H}_{{n}+\mathrm{1}} }{\left({n}+\mathrm{1}\right)^{\mathrm{2}} } \\ $$$$=−\zeta\left(\mathrm{3}\right)+\underset{{n}=\mathrm{1}} {\overset{\infty} {\sum}}\frac{{H}_{{n}} }{{n}^{\mathrm{2}} }=−\zeta\left(\mathrm{3}\right)−\underset{{n}=\mathrm{1}} {\overset{\infty} {\sum}}\frac{\mathrm{1}}{{n}}\int_{\mathrm{0}} ^{\mathrm{1}} {x}^{{n}−\mathrm{1}} \mathrm{ln}\left(\mathrm{1}−{x}\right){dx} \\ $$$$=−\zeta\left(\mathrm{3}\right)+\int_{\mathrm{0}} ^{\mathrm{1}} \frac{\mathrm{ln}^{\mathrm{2}} \left(\mathrm{1}−{x}\right)}{{x}}{dx}=−\zeta\left(\mathrm{3}\right)+\int_{\mathrm{0}} ^{\mathrm{1}} \frac{\mathrm{ln}^{\mathrm{2}} \left({x}\right)}{\mathrm{1}−{x}}{dx} \\ $$$$=−\zeta\left(\mathrm{3}\right)+\mathrm{2}\underset{{n}=\mathrm{0}} {\overset{\infty} {\sum}}\frac{\mathrm{1}}{\left({n}+\mathrm{1}\right)^{\mathrm{3}} }=\zeta\left(\mathrm{3}\right) \\ $$$$\Rightarrow{S}=\zeta\left(\mathrm{3}\right)−\gamma\left(\frac{\pi^{\mathrm{2}} }{\mathrm{6}}−\mathrm{1}\right) \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com